2019
DOI: 10.1002/ird.2381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long‐term Freshwater Irrigation on Soil Fertility

Abstract: Irrigation increases agricultural productivity and inevitably affects soil properties. When irrigation water is of a good quality and does not cause soil salinity or sodicity or contamination, and when there is no soil erosion, a gradual increase in soil fertility under irrigation conditions is, as a rule, expected. However, studies in various countries present examples of a gradual decline in soil fertility under long‐term freshwater irrigation due to leaching of organic matter and exchangeable cations. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…Sustainable practices in the handling of natural resources These contributions are oriented toward the preservation of flora and fauna (handling and consumption), soil improvement practices, organic fertilizers for the sustainable production of crops, handling of natural resources and adequate use and handling of pesticides (Avendaño et al, 2018;Candelaria et al, 2014;Cisneros et al, 2015;Chontal et al, 2019;De Farias et al, 2015;García et al, 2015;Jacinto et al, 2017;Linares et al, 2018;Linares et al, 2017;Llarena et al, 2019;Nikolskii et al, 2019;Ramirez et al, 2016;Vandepitte et al, 2019).…”
Section: Effective Alternatives For Adapting and Mitigating Climate R...mentioning
confidence: 99%
“…Sustainable practices in the handling of natural resources These contributions are oriented toward the preservation of flora and fauna (handling and consumption), soil improvement practices, organic fertilizers for the sustainable production of crops, handling of natural resources and adequate use and handling of pesticides (Avendaño et al, 2018;Candelaria et al, 2014;Cisneros et al, 2015;Chontal et al, 2019;De Farias et al, 2015;García et al, 2015;Jacinto et al, 2017;Linares et al, 2018;Linares et al, 2017;Llarena et al, 2019;Nikolskii et al, 2019;Ramirez et al, 2016;Vandepitte et al, 2019).…”
Section: Effective Alternatives For Adapting and Mitigating Climate R...mentioning
confidence: 99%
“…Soil water content is one of the main limiting factors for forest production, and reasonable irrigation can improve the efficiency of fertilizer utilization [15], while excessive water use may lead to a large amount of leaching of soil nutrients [16,17]. Yu et al found that a large amount of total nitrogen and total phosphorus were lost from bare and agricultural land when rainfall was less than 60 mm [18].…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation not only provides water for the plant but also can influence soil properties. Adequate irrigation management can increase the moisture content of the soil, enhance biological activities as well as the accumulation of organic matter (OM) and increase the efficiency of organic and mineral fertilisers (Nikolskii et al 2019). Under laboratory conditions, S mineralisation was positively correlated with soil moisture content.…”
mentioning
confidence: 99%